Photography : the ultimate guide - Ang, Tom (London, United Kingdom : Dorling Kindersley Limited, 2023)
A comprehensive guide to all things photographic, from amateur snaps to professional-standard portraits. Discover the history behind photography and learn the skills to get the best from your photographs. A comprehensive all-in-one guide, Photography introduces you to the art, history, and culture of photography, and shows you how to take your own fantastic professional-standard photographs. An in-depth guide to all things photographic, Photography opens with a gallery of more than 30 key figures in photography, from 19th-century pioneers to the top photographers working today.
Gallery of photographers -- The story of photography -- Photographic tools -- Elements of photography -- Taking successful photographs -- Working with digital images -- Taking photography further.
Includes index.
Keywords: PHOTOGRAPHY